STRATEGY DEVELOPMENT INDUSTRIALIZATION CULTIVATION OF GROUPER IN SITUBONDO - Ramli Ramli (Samakia : Jurnal Ilmu Perikanan, 2016)
This study aims to identify the condition and potential of grouper aquaculture in the area of Situbondo, determine site development and industrialization of grouper aquaculture development strategy industrialization of grouper aquaculture in Situbondo. Methods used to determine the development strategy is a SWOT analysis, weighting SWOT carried out two assessments, namely (1) Ratings SWOT internally ie on Strength and weakness, which determines the area of industrialization of grouper aquaculture in Situbondo (2) external SWOT namely Opportunity (Opportunity) and threat (Threat) to develop the industrialization of grouper aquaculture in Situbondo. The results showed potential of grouper aquaculture in the district of Situbondo include: (1) potential development of cultivation grouper is still widespread, (2) cultivation technology Grouper been mastered, (3) Human Resource Capacity cultivators groupers is in conformity with the expected competencies, (4) the research institutes and development grouper aquaculture in the District Situbondo namely Center of Aquaculture Brackish Water (BPBAP), (5) the establishment of associations fish of the grouper, (6) the implementation of development programs to cultivators grouper, so it helps increase the capacity and competence of cultivators, (7) marketing costs low because the buyers come directly to farms, (8) facilities and infrastructure such as road access, communication facilities, electricity networks, is available up to the pockets of production and in good condition. Whereas site the industrialization of grouper aquaculture development include: (1) Klatakan village, Kendit Subdistrict, (2) District Panarukan Gelung village, and (3) subdistrict Banyuputih Sumberwaru. While the strategy is development industrialization cultivation Grouper in Situbondo consecutive consisting of S-O (strength-opportunities), S-O (strength-threats), W-O (weaknesses-opportunities), and W-T (weaknesses- threats).